The quantitative study of interfacial contact effects in TEGs by real-topology-based simulations and novel indirect tests. (February 2023) - Gao, Ge; Li, Dou; Gou, Jian-Jun; Gong, Chun-Lin; Li, Shuang-Ming
Highlights: The real-topology-based numerical prediction models of TCR between TE legs and electrodes are established. A novel indirect approach and a corresponding platform of TCR test are developed. Two simplified formulas are proposed to quantitatively express the contact effects on TEG. Abstract: The precise quantitative description of contact effects at heterogeneous interfaces is the crucial issue in developing thermoelectric generators (TEGs) with potential of hypersonic aerodynamic heat harvest. In this paper, the thermal and electrical contact effects between thermoelectric (TE) legs and electrodes are studied by real-topology-based numerical predictions and novel indirect experimental tests, and two simplified formulas are proposed to quantitatively express their effects on TEG. First, the thermal and electrical contact resistances under different temperatures, pressures, gap mediums and thermal radiation conditions are predicted. Second, a novel indirect thermal contact resistance (TCR) test approach relying on the TE conversion characteristics is developed, a corresponding platform is established and the numerical models are then validated. Third, the TE conversion process of TEG is simulated with considering the contact effects by equivalent layers, the TCR test platform is developed to measure the out power of TEG and the numerical models are then validated. Finally, two prediction formulas for the maximum output power prediction of TEGs with considering the contact effects are derived, and good agreement with numerical results is obtained by the maximum deviation of 7.7%.